1986
DOI: 10.1109/tpwrd.1986.4307994
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Assess the Effects of Magnetohydrodynamic Electromagnetic Pulse (MHD-EMP) on Power Systems

Abstract: This paper summarizes a method to evaluate the possible effects of magnetohydrodynamic-eiectromagnetic pulse (MHD-EMP) on power systems. This method is based on the approach adapted to study the impact of geomagnetic storms on power systems. The paper highlights the similarities and differences between the two phenomena. Also presented are areas of concern which are anticipated from MHD-EMP on the overall system operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This injection current was about 15.9 times the normal transformer excitation current. It was also found that for a dc current level equal to 15 times the transformer exciting current, an injection time period of about 15 seconds will be below the threshold of damage 1 .…”
Section: Power System Testing -Three-phase Systems Without a Neutral mentioning
confidence: 99%
See 1 more Smart Citation
“…This injection current was about 15.9 times the normal transformer excitation current. It was also found that for a dc current level equal to 15 times the transformer exciting current, an injection time period of about 15 seconds will be below the threshold of damage 1 .…”
Section: Power System Testing -Three-phase Systems Without a Neutral mentioning
confidence: 99%
“…A large nuclear detonation at altitudes of several hundred kilometers above the earth will distort the earth's magnetic field, resulting in a strong magnetohydrodynamic electromagnetic pulse (MHD-EMP) 1 . This electromagnetic (EM) environment is also referred to as E 3 , since it is the third EM field component-occurring at late times-that characterizes the high-altitude electromagnetic pulse (HEMP) produced by an exoatmospheric nuclear burst.…”
Section: Introductionmentioning
confidence: 99%
“…The induced electric field shown in Fig. 6 was derived by sampling and linear interpolation from the magnetometer data of Legro et al [21] Rackliffe et al [22] also looked at the effects of MHD EMP, as did Klein et al [23] We will describe the power delivery system model for the study of geomagnetic disturbances. The model is based on a time domain simulation algorithm similar to the EMTP (ElectroMagnetic Transients Program).…”
Section: Examination Of the Relative Effects Of Mhd Emp And Solar Stormsmentioning
confidence: 99%
“…Time‐dependent maps of E3 EMP geoelectric fields can, in principle, be obtained by convolving a model of bomb‐generated geomagnetic disturbance with estimates of the Earth‐surface impedance tensor field. In developing such maps, numerical methods pioneered in the 1980s by the Oak Ridge National Laboratory (ORNL) have been widely influential (Barnes, Rizy, et al., 1993; Legro et al., 1985, 1986). ORNL's methods have been used in numerous E3 scenario mapping projects across the conterminous United States (CONUS) (e.g., Electric Power Research Institute, 2017; Electromagnetic Pulse Commission, 2017; Gilbert et al., 2010; International Electrotechnical Commission, 1996; Lee et al., 2019; Rackliffe et al., 1988; Tesche et al., 1991), and these maps have been used in projects for assessing the vulnerability of power grids to the E3 hazard (e.g., Barnes, Tesche, et al., 1993; Electric Power Research Institute, 2019; Electromagnetic Pulse Commission, 2017; Tesche et al., 1991).…”
Section: Introductionmentioning
confidence: 99%